Emergency administration of fibrinogen concentrate for haemorrhage: systematic review and meta-analysis - Yuki Itagaki; Mineji Hayakawa; Yuki Takahashi; Satoshi Hirano; Kazuma Yamakawa (World Journal of Emergency Surgery, 2023)
Abstract Introduction The occurrence of massive haemorrhages in various emergency situations increases the need for blood transfusions and increases the risk of mortality. Fibrinogen concentrate (FC) use may increase plasma fibrinogen levels more rapidly than fresh-frozen product or cryoprecipitate use. Previous several systematic reviews and meta-analyses have not effectively demonstrated FC efficacy in significantly improving the risk of mortality and reducing transfusion requirements. In this study, we investigated the use of FC for haemorrhages in emergency situations. Methods and analysis In this systematic review and meta-analysis, we included controlled trials, but excluded randomized controlled trials (RCTs) in elective surgeries. The study population consisted of patients with haemorrhages in emergency situations, and the intervention was emergency supplementation of FC. The control group was administered with ordinal transfusion or placebo. The primary and secondary outcomes were in-hospital mortality and the amount of transfusion and thrombotic events, respectively. The electronic databases searched included MEDLINE (PubMed), Web of Science, and the Cochrane Central Register of Controlled Trials. Results Nine RCTs in the qualitative synthesis with a total of 701 patients were included. Results showed a slight increase in in-hospital mortality with FC treatment (RR 1.24, 95% CI 0.64–2.39, p = 0.52) with very low certainty of the evidence. There was no reduction in the use of red blood cells (RBC) transfusion in the first 24 h after admission with FC treatment (mean difference [MD] 0.0 Unit in the FC group, 95% CI − 0.99–0.98, p = 0.99) with very low certainty of the evidence. However, the use of fresh-frozen plasma (FFP) transfusion significantly increased in the first 24 h after admission with FC treatment (MD 2.61 Unit higher in the FC group, 95% CI 0.07–5.16, p = 0.04). The occurrence of thrombotic events did not significantly differ with FC treatment. Conclusions The present study indicates that the use of FC may result in a slight increase in in-hospital mortality. While FC did not appear to reduce the use of RBC transfusion, it likely increased the use of FFP transfusion and may result in a large increase in platelet concentrate transfusion. However, the results should be interpreted cautiously due to the unbalanced severity in the patient population, high heterogeneity, and risk of bias.